Accessing hepatitis C direct acting antivirals among people living with hepatitis C: a qualitative study - Tony Antoniou; Cheryl Pritlove; Dana Shearer; Mina Tadrous; Hemant Shah; Tara Gomes (BMC, 2023)
Abstract Background Hepatitis C is curable with direct-acting antivirals (DAAs). However, treatment uptake remains low among marginalized populations such as people who inject drugs. We sought to understand challenges to treatment uptake with DAAs among people living with hepatitis C and compare treatment experiences between people who do and do not inject prescription and/or unregulated drugs. Methods We conducted a qualitative study using focus groups with 23 adults aged 18 years and over who completed DAA treatment or were about to begin such treatment at the time of the study. Participants were recruited from hepatitis C treatment clinics across Toronto, Ontario. We drew upon stigma theory to interpret participants' accounts. Results Following analysis and interpretation, we generated five theoretically-informed themes characterizing the experiences of individuals accessing DAAs: "being 'worthy' of the cure", "spatially enacted stigma", "countering social and structural vulnerability: the importance of peers", "identity disruption and contagion: attaining a 'social cure'" and "challenging stigma with population-based screening". Overall, our findings suggest that structural stigma generated and reproduced through healthcare encounters limits access to DAAs among people who inject drugs. Peer-based programs and population-based screening were proposed by participants as mechanisms for countering stigma within health care settings and 'normalizing' hepatitis C among the general population. Conclusions Despite the availability of curative therapies, access to such treatment for people who inject drugs is limited by stigma enacted in and structured within healthcare encounters. Developing novel, low-threshold delivery programs that remove power differentials and attend to the social and structural determinants of health and reinfection are needed to facilitate further scale up of DAAs and support the goal of eradicating hepatitis C as a public health threat.